2020
DOI: 10.1128/jvi.01522-19
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Conserved Herpesvirus Protein Kinase (CHPK) of Marek’s Disease Alphaherpesvirus in the Skin Reveals a Mechanistic Importance for CHPK during Interindividual Spread in Chickens

Abstract: The Herpesviridae encode many conserved genes, including the conserved herpesvirus protein kinase (CHPK) that has multifunctional properties. In most cases, herpesviruses lacking CHPK can propagate in cell culture to various degrees, depending on the virus and cell culture system. However, in the natural animal model system of Marek’s disease alphaherpesvirus (MDV) in chickens, CHPK is absolutely required for interindividual spread from chicken to chicken. The lack of biological reagents for chicken and MDV ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(45 citation statements)
references
References 74 publications
(110 reference statements)
15
29
0
Order By: Relevance
“…1C). Consistent with previous results, the relative level of CHPKmut was lower compared to CHPKwt under reducing conditions [23]. The relative amount of plaques produced from the virion preps by vCHPKmut was >35-fold lower compared to vCHPKwt samples (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1C). Consistent with previous results, the relative level of CHPKmut was lower compared to CHPKwt under reducing conditions [23]. The relative amount of plaques produced from the virion preps by vCHPKmut was >35-fold lower compared to vCHPKwt samples (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Most CHPK-mutant or -null viruses tested are viable using traditional cell and tissue culture systems [610]. CHPKs have been linked to multiple processes during replication including nuclear egress [1117], tegument association/dissociation [18, 19], viral gene expression [8, 12, 2023], viral DNA replication [12, 16, 17, 2429], DNA damage responses [30, 31], cell-cycle regulation [3235], and evasion of the interferon response [3638].…”
Section: Introductionmentioning
confidence: 99%
“…An important question we were unable to address in this report is the effect of the CHPK mutation (K157A) on the expression of 301B/1 CHPK, since we do not have an antibody against 301B/1 CHPK. In the case of MDV CHPK, it has been shown that the overall protein level of CHPK is diminished, which has been attributed to protein stability [ 59 ]. This was shown using epitope tagged MDV CHPK, and the same approach could be applied in the future to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted from infected FFE cells scraped from FFs or CEC cultures using the QIAamp DNA Mini Kit from Qiagen, LLC (Germantown, MD, USA) according to the manufacturer’s instructions. PCR was performed using DreamTaq Green 2× Master Mix (Thermo Fisher Scientific) and previously described primers to MDV gC and UL13 [ 23 , 24 ]. All PCR reactions were electrophoresed through 0.8% agarose gels and recorded using an Alpha Imager HP (Protein Simple) (Wallingford, CT, USA).…”
Section: Methodsmentioning
confidence: 99%